Pengaruh Kepemimpinan, Lingkungan Kerja dan Motivasi terhadap Kinerja Pegawai pada Kantor BKAD (Badan Keuangan dan Aset Daerah) Kabupaten Sleman The Effect of Leadership, Work Environment and Motivation on Employee Performance at the BKAD Office (Finan - Widyawati, Desty; Supriyadi, Muh (Sekolah Tinggi Ilmu Ekonomi Bisnis dan Perbankan, 2023)
This study aims to determine: (1) the influence of leadership on the performance of employees of the Sleman Regency Regional Financial and Asset Management Agency, (2) the influence of the work environment on the performance of employees of the Regional Finance and Asset Management Agency of Sleman Regency, (3) the effect of motivation on the performance of employees of the Regional Finance and Asset Management Agency, and Regional Assets of Sleman Regency, (4) influence of leadership, work environment, and motivation on the performance of employees of the Sleman Regency Regional Finance and Asset Agency.This study used a quantitative approach to 318 respondents, consisting of Civil Servants and Non Civil Servants of BKAD Sleman Regency in 2023. By distributing using a questionnaire. The instrument test uses validity and reliability tests. The data analysis technique used is Multiple Linear Regression analysis.The results showed that: (1) motivation has a positive and significant effect on employee performance (2) leadership has a positive and significant effect on employee performance (3) work environment has a positive and significant effect on employee performance. (4) leadership, work environment and motivation simultaneously have a positive effect on employee performance. When viewed from the overall effect of these variables is 68.7%, the remaining 31.3% is influenced by other factors not discussed in this study